Student's Understanding of Concepts Based on APOS Theory on the material of triangles and quadrilaterals in terms from the level of mathematical ability - Mayang Sari (Center of Education Journal (CEJou), 2024)
The purpose of this study was to analyze the concept understanding of APOS theory (Action, Process, Object, Schema) on the material of triangles and quadrilaterals in terms from the level of mathematical ability. This research uses qualitative research methods with descriptive data. This research is a class VIII A student with a total of 28 students who are taken as research subjects consisting of three students with high, medium and low understanding ability categories based on student score data collected while teaching by the math teacher and subject selection suggestions from the math teacher. This research data analysis technique includes data reduction, data display, donclusion. The results of the research and discussion can be concluded that concept understanding in terms of APOS theory in students is as follows. High ability subjects are able to reach the action, process, object, and scheme stages. Medium ability subjects can reach the action, process, object stages, although the object stage is still not perfect, and cannot reach the scheme stage. Low ability subjects were only able to reach the action, process, although the process stage was not perfect in doing so, and had not yet reached the object and scheme stages.